Clustering shrimp farms in Bangladesh: A novel effort with mixed outcomes - Kabir, Razin; Belton, Ben; Narayanan, Sudha; Sakil, Abdul Zabbar; Khan, Asraul Hoque; Hernandez, Ricardo (International Food Policy Research Institute, 2025)
Organizing smallholder farmers in clusters has been widely promoted as a way to boost agricultural productivity, streamline delivery of extension services, and improve access to markets. In Bangladesh, where shrimp is an important export crop produced largely by smallholders, government and industry view clustering as key to preventing Bangladesh being left behind in an increasingly competitive global market. Bangladesh’s shrimp exports are highly dependent on the hotel, restaurant, and catering (HoReCa) sector in Europe—a small and relatively low value market segment. Gaining access to the much larger and potentially more lucrative retail market segment in Europe and North America requires high quality, traceable, and - increasingly - certified, shrimp, posing a challenging for Bangladesh.